Analisis Semantik Kata Nafaqah Dalam Surah An-Nisa Ayat 34 dan Relevansi Terhadap Putusan Nafkah Pengadilan Agama Indonesia - Pipin Novrianti (Suria Academic Press, 2025)
Maintenance is a fundamental obligation in Islamic family law, serving to maintain the continuity and well-being of the household. The concept of maintenance has a strong normative basis in the Qur'an, particularly Surah An-Nisa', verse 34, which links the obligation to provide maintenance to the husband's leadership responsibilities (qiwāmah). This study aims to analyze the semantic meaning of the word